2013
DOI: 10.1097/adm.0b013e318279756f
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Clinical Data, and Treatment of Viral Hepatitis in a Large Cohort of Intravenous Drug Users

Abstract: Our results show that (a) the majority of IDUs in Greece have chronic hepatitis C and the prevalent genotype is 3 (b) patients who complete therapy have SVR rates similar to those without drug-dependence, and (c) since IDUs constitute the core of the hepatitis C epidemic and the main route of HCV transmission, efforts to treat these patients should be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…The most prevalent HCV genotype in this study was genotype Type III. In recent studies done in Iran, the most prevalent genotype, was Type III[34] and studies in other countries including, Saudi Arabia revealed genotype IV as the most prevalent,[567] genotype Type II in Chinese and Brazilian prisoners,[89] Type II in Greek IVDUs[10] and Type I in other Countries. [11112]…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent HCV genotype in this study was genotype Type III. In recent studies done in Iran, the most prevalent genotype, was Type III[34] and studies in other countries including, Saudi Arabia revealed genotype IV as the most prevalent,[567] genotype Type II in Chinese and Brazilian prisoners,[89] Type II in Greek IVDUs[10] and Type I in other Countries. [11112]…”
Section: Discussionmentioning
confidence: 99%
“…After treatment was made available in the OST clinic 85 patients (25%) commenced therapy [ 24 ]. Gigi et al demonstrated higher rates of treatment uptake in an OST clinic compared to a tertiary hospital clinic (61% vs 55%) [ 25 ]. To our knowledge, the only randomised trial regarding the impact of placement of HCV treatment services in OST clinics on treatment uptake was conducted by Bruce et al, and included modified directly observed therapy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In overall pooled studies and in studies conducted in countries other than Egypt, the risk factor of strongest association was IDUs, followed by IDU partner, HIV and HBV infections. This holds true in pooled studies done in Egypt and reinforces the significance of this form exposure being the most important factor contributing to HCV spread . Nevertheless, the present results are at variance with a recent MA by Mahmoud et al ., 2013 who reported that the contribution of IDU to HCV prevalence is much lower in Egypt than in other countries where transmission is mainly associated with medical exposures .…”
Section: Discussionmentioning
confidence: 99%